1994
DOI: 10.1177/096032719401300705
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled tert-Butyl Acetate and its Metabolite tert-Butyl Alcohol Accumulate in the Blood during Exposure

Abstract: 1 A continuous 5 h-exposure to approximately 440 ppm tert-butyl acetate in air (via a tracheal canule) resulted in continuously increasing concentrations of tert-butyl acetate and tert-butyl alcohol (metabolite of tert-butyl acetate) in the blood of rats. 2 This accumulation of tert-butyl acetate and tert-butyl alcohol was reproduced during a continuous exposure to about 900 ppm tert-butyl acetate in air over a period of 4 h and 15 min. After the inhalation approximately 50% of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Deaths from exposures to TBAC below 400 ppm have not been confirmed in four independent studies: (1) Groth and Freundt [17] -no deaths at 440 ppm for 5 h or 900 ppm for 4 h; (2) Stillmeadow [16] -no deaths at 470 ppm; (3) current metabolism study -no deaths at 1000 ppm; (4) current acute inhalation study -no deaths at 1873 ppm. Therefore, we carefully examined the IBT study and found the following problems:…”
Section: Acute and Subacute Toxicity Of Tbacmentioning
confidence: 99%
“…Deaths from exposures to TBAC below 400 ppm have not been confirmed in four independent studies: (1) Groth and Freundt [17] -no deaths at 440 ppm for 5 h or 900 ppm for 4 h; (2) Stillmeadow [16] -no deaths at 470 ppm; (3) current metabolism study -no deaths at 1000 ppm; (4) current acute inhalation study -no deaths at 1873 ppm. Therefore, we carefully examined the IBT study and found the following problems:…”
Section: Acute and Subacute Toxicity Of Tbacmentioning
confidence: 99%
“…The metabolism of inhaled TBAc was studied in Sprague-Dawley rats by Groth and Freundt (1994). A continuous 5 h exposure to approximately 440 ppm TBAc (via a tracheal canula) resulted in continuously increasing blood concentrations of TBAc and tert-butanol (TBA), a metabolite of TBAc.…”
Section: Key Studies: Metabolismmentioning
confidence: 99%
“…It has been established that TBAc is metabolized in rats to TBA (Groth and Freundt, 1994). Oral TBA exposure has been demonstrated to induce renal tumors in male rats and thyroid follicular cell tumors in female mice (NTP, 1995).…”
Section: Male Rat Kidney Tumor Datamentioning
confidence: 99%
“…It has excellent solvency for a variety of substances. Therefore, TBAc is mainly used for architectural coatings, industrial cleaning, and as a solvent in paints and lacquers (Groth and Freundt,1994 ; Budroe et al, 2004 ; Yang et al, 2007) . Moreover,TBAc has recently been exempted from the definition of a volatile organic compound (VOC) by both the Air Resources Board (ARB) and the local air pollution control and air quality management agencies.…”
Section: Introductionmentioning
confidence: 99%